2021
DOI: 10.1186/s13102-021-00351-8
|View full text |Cite
|
Sign up to set email alerts
|

Engaging people with long-term health conditions in a community-based physical activity initiative: a qualitative follow-up study evaluating the parkrun PROVE project

Abstract: Background The “parkrun: running or volunteering for everyone” (PROVE) project was an example of a community-based physical activity and volunteering initiative for people living with long-term health conditions in England. The 3 year project involved appointing volunteer Outreach Ambassadors whose role was to promote parkrun to people living with long-term health conditions through various outreach activities. This qualitative study aimed to understand the experience of delivering the project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Previous research has demonstrated that for equitable participation in parkrun events in England, it is not enough to situate (more) parkrun events in areas of high socio-economic deprivation and expect this to translate into participation by people from the local neighbourhood [ 27 ] or underrepresented communities. A small number of parkrun studies have explored outreach and inclusivity issues [ 19 , 37 ] and the current findings demonstrate the outreach activities that are possible. The outreach activities implemented by parkrun Ambassadors were consistent with practice in community development (utilising community assets and understanding the needs of local people) [ 38 ], but were limited in scope, reach and scalability by resource constraints.…”
Section: Discussionmentioning
confidence: 51%
“…Previous research has demonstrated that for equitable participation in parkrun events in England, it is not enough to situate (more) parkrun events in areas of high socio-economic deprivation and expect this to translate into participation by people from the local neighbourhood [ 27 ] or underrepresented communities. A small number of parkrun studies have explored outreach and inclusivity issues [ 19 , 37 ] and the current findings demonstrate the outreach activities that are possible. The outreach activities implemented by parkrun Ambassadors were consistent with practice in community development (utilising community assets and understanding the needs of local people) [ 38 ], but were limited in scope, reach and scalability by resource constraints.…”
Section: Discussionmentioning
confidence: 51%
“…Parkrun was considered to be inclusive but there is more to be done to ensure accessibility for everyone, such as logistics, policies and resources to support people with long-term health conditions 26. A qualitative follow-up study (n=11) evaluated the impact of PROVE and made recommendations for similar projects; one of these recommendations was to realise the target population and ensure efficient ways to reach them 27…”
Section: Discussionmentioning
confidence: 99%
“… 26 A qualitative follow-up study (n=11) evaluated the impact of PROVE and made recommendations for similar projects; one of these recommendations was to realise the target population and ensure efficient ways to reach them. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient advisory boards (PABs) are a statutory part of rehabilitation institutions to meet these patient-centered demands. Noting the lack of general rules or procedures for PABs, Sagen et al [ 21 ] conducted an exploratory study to learn how patient representatives experienced their organization, influence and impact. Findings confirmed that rehabilitation institutions improved with enduring PPI via PABs, further suggesting that rigorous evaluation must continue to ensure continued quality.…”
Section: Introductionmentioning
confidence: 99%